THE BUILDING AND IMPLANTATION OF NATIONAL POLITICS FOR INTEGRATIVE AND COMPLEMENTARY PRACTICES IN THE UNIQUE HEALTH SYSTEM AND THE MEDICINAL PLANTS’ AND PHYTOTHERAPICS’ NATIONAL POLITICS. (Revista de Ciências Agroveterinárias, 2006)
Interview with Dr. Ângelo Giovani Rodrigues.
Keywords: Interview; Ângelo Giovani Rodrigues